2019
DOI: 10.36709/jte.v4i4.13972
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Students’ Motivation and Their Speaking Achievement at English Department of Halu Oleo University

Abstract: This research focuses on the correlation between students’ motivation and their speaking achievement. The research conducts in Halu Oleo University, English Department at academic year 2017/2018 that have pass Speaking III to see their motivation and speaking achievement. There are 36 students taken as sample. The data of the research collect through close-ended questionnaire adapted from Gardner (1985) who had developed the Attitude/Motivation Test Battery (AMTB) to get the data of students’ motivation index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Three interrelated instrumental motivations when students learn English include future studies, grades, and careers. Another previous study by Fatimah, Sale & Sapan (2019), they conducted "The Correlation between Students' Motivation and Their Speaking Achievement at English Department of Halu Oleo University". The study showed that there is a significant correlation between students' motivation and their speaking achievement, and During Covid-19 Pandemic students are instrumentally motivated higher than integratively.…”
Section: Introductionmentioning
confidence: 99%
“…Three interrelated instrumental motivations when students learn English include future studies, grades, and careers. Another previous study by Fatimah, Sale & Sapan (2019), they conducted "The Correlation between Students' Motivation and Their Speaking Achievement at English Department of Halu Oleo University". The study showed that there is a significant correlation between students' motivation and their speaking achievement, and During Covid-19 Pandemic students are instrumentally motivated higher than integratively.…”
Section: Introductionmentioning
confidence: 99%